Manajemen Literasi Digital Syariah dalam Pengembangan Ekosistem Ekonomi Kreatif Halal di Kalangan Pelajar - Putriningsih, Saniyah; Anis Nala Falikhah; Tiara Ningrum; Amalia Amiza; Wafika Erininda; Mohammad Azimul Wafa; Hendri Hermawan Adinugraha (Welfare : Jurnal Pengabdian Masyarakat, 2026)
Advances in information technology have opened up new opportunities in the development of a halal creative economy that is relevant to the younger generation. This community service programme aims to equip students at Madrasah Aliyah Hishna in Pekalongan City with a comprehensive understanding of sharia digital literacy and the ability to apply it in supporting the halal creative economy ecosystem. The activity was conducted through interactive education that covered an introduction to the concept of the halal creative economy, the use of digital platforms as a promotional medium, and the instilling of social media ethics. The implementation began with school coordination, material preparation, and the delivery of education, and was concluded with an evaluation of the participants' understanding. Results showed high enthusiasm, active participation, and measurable improvement in understanding through quizzes. Participants were able to see digital literacy not only as a means of productivity but also as a medium for spreading Shariah values. This activity fostered new awareness and opened opportunities for students to become innovative and ethical actors in the halal creative economy.